Sensory perception of dead conspecifics induces aversive cues and modulates lifespan through serotonin in Drosophila - Tuhin S. Chakraborty (Nature Portfolio, 2019)
Different sensory experiences can affect longevity in Drosophila. Here the authors find that exposure of Drosophila directly to dead conspecifics affects longevity via a serotonergic mechanism, and that Drosophila exposed to dead conspecifics also become an aversive stimulus to naïve choosers.